Economic Analysis of Papaya Farming in Chitradurga: Production and Marketing Perspectives - Veershetty,; , Jagadeesh M S; , B Manjunatha; , Thejashwini S; , S Siddayya; , Abhishek G J (Archives of Current Research International, 2024)
In India, papaya cultivation thrives as a vibrant testament to the nation's rich agricultural diversity, offering both economic promise and nutritional benefits. With its lush, tropical appeal and versatile uses, papaya stands out as a key player in the country's fruit sector, captivating farmers and consumers alike with its sweet, succulent offerings. This study presents an economic analysis of papaya farming in Chitradurga, focusing on production costs, returns, and marketing perspectives. The research aimed to identify the key economic factors influencing papaya cultivation and marketing efficiency. The methodology involves calculating cost of cultivation with detailed assessments of marketing channels and constraints. The findings revealed that the total cost of papaya cultivation was Rs. 3,58,998.19 per hectare, with labour-intensive practices contributing significantly to the overall expenses. The study found a gross return of Rs. 8,90,784.69 per hectare and a net profit of Rs. 5,31,786.50 per hectare, indicating profitable cultivation. Among the marketing channels, Channel-I (Producer → Pre-harvest contractor → Wholesaler → Retailer → Consumer) was the most prevalent, though it involved higher marketing costs. The primary production constraints identified were fruit dropping, inadequate quality seedlings, and pest damage, while marketing constraints included price fluctuations and lack of demand during peak seasons. These results underscore the need for improved management practices and marketing strategies to enhance profitability and address key challenges in papaya farming.